Os desafios do desenvolvimento e da inclus\~ao social: O caso do arranjo político-institucional do programa nacional de produç\~ao e uso do Biodiesel - Paula Maciel Pedroti (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– The article analyses the Programa Nacional de Produç\~ao e Uso do Biodiesel (PNPB), an agro-energy policy with social aims, through the study of the political and technical capabilities of its institutional arrangement. The article verifies if the arrangement is able to combine the demands of democratic context (such as transparency, control and social participation) with the technical elements needed to conduct this policy efficiently. It also analyses the contribution of the PNPB's arrangement in the accomplishment of two goals: the creation of the biodiesel market and the social inclusion in the productive chain of the sector.
Keywords: Z18; Q48; Q16; 330; biodiesel; agro-energy; development; social inclusion; family farming; Programa Nacional de Produç\~ao e Uso do Biodiesel